Competence-based approach in education: essence and methods of implementation in the educational process - Romanovskyi, O. G.; Mykhaylychenko, V.; Kobets, V. (Impressum, 2020)
The article reveals the content of the competence-based approach, analyzes the concepts of "competence" and "competency". It is shown that its implementation in the education system is constrained by the ineffective organization of students' self-study and insufficient theoretical development of new constructs. The content of the readiness of future specialists for professional activity, and the role of the competence-based approach in its improvement are revealed. The necessity of developing a common understanding of the content of qualifications in terms of competencies, the creation of models of different levels of competences, the introduction of innovative psychological and pedagogical technologies into the educational process, as well as teaching aids for their use, is shown. Recommendations aimed at improving the effectiveness of the self-study of future specialists in the learning process are proposed: increasing volume of the self-study, methods, and techniques of activating of its organizing, as well as activating of internal resources of the individual.
Keywords: competence-based approach; competence; competency; educational process; future specialist; knowledge; skills; abilities; self-study